Fabrication And Properties Of Electromagnetic Interferences Shielding Epoxy Composites For Electronic Packaging Application - Phan, Chee Hong (2015)
Rapid development in wireless commination devices was lead to seriousness in electromagnetic pollution. The main aim of this study is develop an effective electromagnetic interferences (EMI) shielding composites for electronic packaging application. In the present study, an EMI shielding epoxy composites have been fabricated by incorporated both multiwalled carbon nanotubes (MWCNTs) and manganese zinc ferrites (MnZn ferrites) in epoxy matrix. MWCNTs was functionalized with concentrated nitric acid with various functionalization reaction time. MWCNTs with 2 hours functionalization treatment shows enhancement in colloidal suspension stability, dispersion, electrical conductivity, dielectric properties and EMI shielding effectiveness (SE) as compared with pristine MWCNTs. This is due to presence of oxygenic functional groups on the surface of nanotube as observed within Fourier transform infra-red spectroscopic spectra. However, the properties of functionalized MWNCTs/ epoxy composites decrease for more than 2 hours treatment due to extensive damage of its structure as verified with Raman spectroscopy. In the second part of the study, MnZn ferrite was synthesized via citrate gel method with various calcination temperature. It is found that as the calcination temperature increases, the higher phase purity and larger particle size of MnZn ferrite were obtained. MnZn ferrite nanoparticle calcinated at 1000 °C exhibited the highest phase purity with average particle size of 856.4 nm. In the study of functionalized MWCNTs/ MnZn ferrite epoxy composite, fillers ratio of 3:1 showed the highest EMI SE and the shielding mechanism of the composite was dominated by absorption. It is observed that the EMI shielding effectiveness of composites were increased with the filler loading and composites thickness. It is also found that the EMI shielding performance of 2.0 mm fabricated composite, with the filler loading of 4.0 vol.% and applied of conductive back-layer, was comparable with commercial EMI shielding gaskets/pads. Maximum SE of 65 dB at 9 GHz was obtained for the EMI shielding polymer composites produced in the present study.